Ultrasonic cardiogram and MiRNA-21 analysis of cardiac dysfunction in patients with cardiac arrest following cardiopulmonary resuscitation. (July 2020) - Liu, Xing; Zhang, Yongguang; Jiang, Peng; Cai, Jiachen; Fu, Qiuhong; Li, Xiaolei; Li, Zhou
Highlights: There are few studies on miRNA-21 in cardiac dysfunction after cardiopulmonary resuscitation. This study combines imaging, pathophysiology and cardiac electrophysiology to confirm the expression of microRNA21 in cardiac dysfunction after cardiopulmonary resuscitation. Because of the multidisciplinary evidence, the research is more convincing. ECG, color Doppler echocardiography and myocardial enzymes are very common examinations and tests, which will not bring more pain and cost to patients. The detection of MiRNA-21 is simple and feasible, and can be carried out in any laboratory. It can be used to evaluate the severity of cardiac dysfunction in patients after cardiopulmonary resuscitation quickly and conveniently. Abstract: Purpose: To explore correlations between the serum level of miRNA-21 expression and cardiac dysfunction severity after cardiopulmonary resuscitation (CPR) using ultrasonic cardiogram. Methods: Thirty-nine patients with cardiopulmonary arrest receiving successful CPR and forty-one healthy participants were recruited in the study. Reverse Transcription-Polymerase Chain Reaction (RT-PCR) and immunochemiluminometric assays was used to examine the serum miRNA-21 level and the concentration of cardiac troponins T and I, respectively. Indices of Electrocardiogram (ECG) and cardiac dysfunction measured by ultrasound of patients in the case group were used to assess cardiac function after CPR. Furthermore, the correlation between the serum level of miRNA-21 expression and severity of cardiac dysfunction was analyzed by Spearman correlation analysis. Results: As compared to the control group, the serum level of miRNA-21 expression, as well as cardiac troponin T and I levels in the case group were significantly higher ( p  = 0.000). The miRNA-21 expression level in the patients at IV grade of cardiac function were substantially higher than patients at III grade ( p  = 0.015). There was no significant difference in level of cardiac troponins T and I between patients at III grade and patients at IV grade ( p  > 0.05). Further, Spearman correlation analysis revealed that the level of miRNA-21 expression was negatively correlated with cardiac function index in the ultrasound imaging: E peak, E/A value, LVEF and LVEDD ( r  = 0.617, 0.535, 0.612, 0.573, P  = 0.012, 0.009, 0.008, 0.011), but was positively correlated with the level of cardiac troponins T and I ( r  = 0.546, 0.582, P  = 0.006, 0.007) and the severity of cardiac dysfunction ( r  = 0.859, p  < 0.05). Conclusion: The level of miRNA-21 is higher after CPR is closely related to the severity of cardiac dysfunction that is measured by ultrasound, suggesting that it may serve as a potential biomarker.